2015
DOI: 10.5229/jecst.2015.6.2.50
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review on Non-Aqueous Lithium-Oxygen Batteries - Electrochemistry and Cathode Materials

Abstract: There is a great deal of current interest in the development of rechargeable batteries with high energy storage capability due to an increasing demand for electric vehicles (EVs) with driving ranges comparable to those of gasoline-powered vehicles. Among various types of batteries under development, a Li-O 2 battery delivers the highest theoretical energy density; thus, it is considered a promising energy storage technology for EV applications. Despite the fact that extensive research efforts have been made in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…In general, the limited cyclic performance of Li–air cells is associated with three factors: the accumulated reaction products in the air electrode, the instability of the anode, and the evaporation of the electrolyte. In Li–air batteries with organic electrolytes, the solid reaction products formed during the discharging process do not completely dissociate during the charging process, and therefore accumulate on the surface of the air electrode. In particular, unwanted products from parasitic reactions, such as Li 2 CO 3 formed from the reaction between Li 2 O 2 and C, and organic materials (CH 3 CO 2 Li, HCO 2 Li, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the limited cyclic performance of Li–air cells is associated with three factors: the accumulated reaction products in the air electrode, the instability of the anode, and the evaporation of the electrolyte. In Li–air batteries with organic electrolytes, the solid reaction products formed during the discharging process do not completely dissociate during the charging process, and therefore accumulate on the surface of the air electrode. In particular, unwanted products from parasitic reactions, such as Li 2 CO 3 formed from the reaction between Li 2 O 2 and C, and organic materials (CH 3 CO 2 Li, HCO 2 Li, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Commercial batteries cannot meet the requirements of large-scale applications such as electric vehicles. Li–air batteries have attracted enormous research attention as a promising alternative because of their high theoretical energy density. However, there are still several obstacles that must be overcome before their practical application becomes feasible. The basic reactions of nonaqueous Li–air batteries are the formation of Li 2 O 2 during the discharging process and its dissociation during the charging process (i.e., 2Li + + O 2 ⇔ Li 2 O 2 ) on the surface of air electrode. One of the major issues in the use of nonaqueous Li–air batteries is that the dissociation of solid, insulating Li 2 O 2 is slow and inefficient because of the poor electron transport between the Li 2 O 2 particles and the electrode surface. This kinetic limitation in nonaqueous Li–air batteries results in undesirable electrochemical properties such as large overpotential, low rate-capability, and limited cyclic performance.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that CP_12 h shows a tremendous increase in Q of nearly 28% to 140% at 0.1 mA/cm 2 and 1.0 mA/cm 2 than that of CP_4 h, being consistent with the described increase in specific surface area and the introduction of microporosity. The latter is deemed to be beneficial for the transport of oxygen [37] and ion diffusion. These results show that the pore structure with micropores (on the surface of carbon fibers) and macropores (already present as free space between fibers) are supportive for catalytic activity for oxygen reduction reaction.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…h shows a tremendous increase in Q of nearly 28 % to 140 % at 0.1 mA/cm 2 and 1.0 mA/cm 2 than that of CP_4 h, being consistent with the described increase of specific surface area and the introduction of microporosity. The latter is deemed to be beneficial for the transport of oxygen [43] and ion diffusion. These results show that the pore structure with micropores (on the surface of carbon fibers) and macropores (already present as free space between fibers) are supportive for catalytic activity for oxygen reduction reaction.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%